2020
DOI: 10.5603/gp.a2020.0012
|View full text |Cite
|
Sign up to set email alerts
|

Unscarred uterine rupture and subsequent pregnancy outcome — a tertiary centre experience

Abstract: Objectives: The aim of this study was to investigate the incidence, etiology and obstetric outcomes of rupture in unscarred uterine rupture and in those with a history of uterine rupture Material and methods: The hospital records of women who had delivered between May 2005 and May 2017 at a tertiary center were examined retrospectively. Data on patients with unscarred uterine rupture in pregnancy who had undergone fertility-preserving surgery were evaluated. Results: During the study period, 185,609 deliveries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…In such cases, poor results such as hysterectomy, hypogastric artery ligation, and relaparotomy have been reported. [31][32][33][34] In our finding, almost half of the operation (50.8%) was conducted by emergency surgeons and 49.2% by senior obstetricians. DDI attainment less than 30 minutes was 6.2% vs 29.1%, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…In such cases, poor results such as hysterectomy, hypogastric artery ligation, and relaparotomy have been reported. [31][32][33][34] In our finding, almost half of the operation (50.8%) was conducted by emergency surgeons and 49.2% by senior obstetricians. DDI attainment less than 30 minutes was 6.2% vs 29.1%, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…It is a strong predictor of uterine scar defects in women with a previous caesarean section [14,15]. It has been suggested that the risk of recurrent uterine ruptures can be reduced by elective caesarean section at 36-37 weeks gestational age, in women with a history of isthmic rupture, and at 32-33 weeks gestational age after foetal lung maturation in women with a history of fundal uterine rupture and those with short inter-pregnancy intervals [16]. However, there is currently no gold standard for diagnosing caesarean scar dehiscence [11].…”
Section: Discussionmentioning
confidence: 99%
“…4 Similar to the study by Nurullah Peker et al in which more than half (56.7%) of cases under went hysterectomy, the present study also had more than half (55.5%) cases who underwent hysterectomy. 8,9 In most of the patient's rupture occurred in the lower uterine segment and hysterectomy was performed in most of them.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the risk factors for unscarred uterine rupture are: high parity, use of uterotonic drugs, advanced maternal age, dystocia, macrosomia and possibly short inter-pregnancy intervals. [7][8][9][10][11] High incidence in this study is a reflection of prolonged trial of labour at home, delay in referral of the cases from peripheral health centers and further delay due to poor transport facilities in the rural area. A high index of suspicion should be held when labor involves unbooked patients, grand multiparity, or previously scarred uterus.…”
Section: Discussionmentioning
confidence: 99%